“I Did Not Know Then...” Two Autothematic Poems - Pasterski, Janusz (Tematy i Konteksty, 2021)
The author discusses the autothematic motifs in the poems Sitowie by Julian Tuwim and Przeciwne wiatry by Tomasz Różycki. The author analyses both poems and compares the transformations of the autothematic motifs, emphasizing the connections with literary tradition and the dialogue of the poets’ artistic attitudes. In both literary works the key problem is the relation between words and things.